'Tweaking' the model for understanding and preventing maternal and neonatal morbidity and mortality in Low Income Countries: "inserting new ideas into a timeless wine skin". Issue 1 (December 2016) - Mwaniki, Michael; Baya, Evaline; Mwangi-Powell, Faith; Sidebotham, Peter
Abstract Background Maternal and neonatal morbidity and mortality in Low Income Countries, especially in sub-Saharan Africa involves numerous interrelated causes. The three-delay model/framework was advanced to better understand the causes and associated Contextual factors. It continues to inform many aspects of programming and research on combating maternal and child morbidity and mortality in the said countries. Although this model addresses some of the core areas that can be targeted to drastically reduce maternal and neonatal morbidity and mortality, it potentially omits other critical facets especially around primary prevention, and pre- and post-hospitalization continuum of care. Discussion The final causes of Maternal and Neonatal mortality and morbidity maybe limited to a few themes largely centering on infections, preterm births, and pregnancy and childbirth related complications. However, to effectively tackle these causes of morbidity and mortality, a broad based approach is required. Some of the core issues that need to be addressed include:-i) prevention of vertically transmitted infections, intra-partum related adverse events and broad primary prevention strategies, ii) overall health care seeking behavior and delays therein, iii) quality of care at point of service delivery, and iv) post-insult treatment follow up and rehabilitation. In this article we propose a five-pronged framework that takes all the above into consideration. This frameworks further builds on the three-delay model and offers a more comprehensive approach to understanding and preventing maternal and neonatal morbidity and mortality in Low Income Countries Conclusion In shaping the post 2015 agenda, the scope of engagement in maternal and newborn health need to be widened if further gains are to be realized and sustained. Our proposed five pronged approach incorporates the need for continued investment in tackling the recognized three delays, but broadens this to also address earlier aspects of primary prevention, and the need for tertiary prevention through ongoing follow up and rehabilitation. It takes into perspective the spectrum of new evidence and how it can be used to deepen overall understanding of prevention strategies for maternal and neonatal morbidity and mortality in LICS.